A novel SOX9 H169Q mutation in a family with overlapping phenotype of mild campomelic dysplasia and small patella syndrome. Issue 10 (16th August 2013) - Matsushita, Masaki; Kitoh, Hiroshi; Kaneko, Hiroshi; Mishima, Kenichi; Kadono, Izumi; Ishiguro, Naoki; Nishimura, Gen
Abstract The phenotypic similarities have been demonstrated between non‐lethal campomelic dysplasia (CD) and small patella syndrome (SPS), in which different genetic defects have been identified. We report on a familial case of skeletal dysplasia with overlapping phenotype of mild CD and SPS, including defective ischio‐pubic ossification, elongated femoral neck, hypoplastic patellae, and increased space between the first and the second toes (sandal gap). Direct sequencing analysis demonstrated a novel missense mutation (p.H169Q) within the coding region of the SOX9 gene and negative for TBX4 mutations. Functional analysis of the p.H169Q mutant revealed reduced but not fully abolished transactivation capacity of the mutated protein. Retained residual SOX9 function might contribute to an extremely mild CD phenotype in the present cases. © 2013 Wiley Periodicals, Inc.